2021
DOI: 10.1042/bsr20202022
|View full text |Cite|
|
Sign up to set email alerts
|

Red algae natural products for prevention of lipopolysaccharides (LPS)-induced liver and kidney inflammation and injuries

Abstract: Background: The liver and kidney inflammation due to bacterial infection is one of the most common pathological problems leading to tissue damage or disease. In many liver and kidney disorders, which represent serious global health burden with a high economic cost, oxidative stress-related inflammation and apoptosis are important pathogenic components, finally resulting in acute liver and/or kidney failure. Erythropoietin and its analogues are well known to influence the interaction between apoptosis and infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 66 publications
(85 reference statements)
2
11
0
Order By: Relevance
“…As a result, it induces acute inflammation in multiple organs, including the kidney, brain, lung, and liver [ 43 ]. Thus, several studies have investigated the anti-inflammatory effects of natural products, compounds, or drugs using LPS-induced animals as models of acute inflammation [ 44 , 45 , 46 , 47 ]. Recently, we reported that the partial replacement of SFAs in a high-fat diet (HFD) with PUFAs such as perilla oil (PO) or corn oil at a converted dose (2–8%) suppressed insulin resistance and nuclear factor κ-light-chain-enhancer of activated B cells (NF-κB) signaling pathways, and enhanced antioxidant enzyme expression in rats [ 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, it induces acute inflammation in multiple organs, including the kidney, brain, lung, and liver [ 43 ]. Thus, several studies have investigated the anti-inflammatory effects of natural products, compounds, or drugs using LPS-induced animals as models of acute inflammation [ 44 , 45 , 46 , 47 ]. Recently, we reported that the partial replacement of SFAs in a high-fat diet (HFD) with PUFAs such as perilla oil (PO) or corn oil at a converted dose (2–8%) suppressed insulin resistance and nuclear factor κ-light-chain-enhancer of activated B cells (NF-κB) signaling pathways, and enhanced antioxidant enzyme expression in rats [ 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…Data presented by Nabil-Adam and Shreadah suggested that the marine extract of Galaxaura oblongata could have nutraceutical and pharmaceutical applications because of its promising therapeutic agents against LPS-induced acute kidney injuries through antioxidant and anti-inflammatory mechanisms of action, although further studies are required [70].…”
Section: Marine Algaementioning
confidence: 99%
“…Samples were cleaned with fresh tap water and the epiphytes were removed completely. The cleaned samples were shade-dried at room temperature and well ground [18][19].…”
Section: Study Area and Collection Of P Pavonicamentioning
confidence: 99%
“…P. pavonica can be used for its antioxidants, antimicrobial, insecticidal, antibiotics, hypo-allergic, hepatoprotective anti-inflammatory and antidiabetic activities [15][16]. P. pavonica seaweeds' anti-inflammatory and antioxidant properties are well-known for their medical use [17][18][19]. It is a source of bioactive metabolites that are not found in other species and is used in the pharmaceutical industry.…”
Section: Introductionmentioning
confidence: 99%